The Role in Reducing External Audit of Creative Accounting Practice of Financial Statements and their Impact on the Auditor's Report – An Empirical Study of a number of Saudi companies to contribute to the stock market – - Al-Sammarraee, Ammar Esam; Al-shareeda, Nadya Abduljabbar (Journal of Economic, Administrative and Legal Sciences, 2021)
The science of accounting principles and profession internationally recognized standards (GAAP) must therefore abide by to maintain the confidence gained during the many decades of time and place that it reached this profession needed interesting the Internal and external Audit.The economic collapses of the firms in the world have impacted negatively on the confidence in the profession and its principles and standards.In this context we reached the following results:The importance of the moral dimension of accountants because of built decisions on the results of creative accounting practices and the importance of credibility in the financial statements and this does not mean that the importance of the artistic dimension to the accounting profession, The methods used in the creative accounting in the companies under study of relatively great importance on the credibility of the financial statements by the standard used to study, Observed convergence in consensus that the study sample agree that creative accounting methods have an impact on the credibility of the financial statements and that there was no significant dispersion in the answers of respondents and this shows the negative impact on businesses and the economy in general as a result of these practices.The main recommendations researcher:The need to identify all the creative accounting practices in order to find appropriate solutions., The necessity of activating the awareness of the ethical dimension of the accounting profession as it has the greatest impact in the production of lists of highly credible financial benefit to the economy in general and on the relative development and continuation of the companies., The necessity of activating the powers granted to external auditors and develops pieces of legislation governing the work of accounting so that they can adjust the fraud, manipulation and detection of errors., The need to adjust and legalizing illegal practices of creative accounting and modernize the laws regarding legal practices because of their relatively great importance.
Keywords: external audit; creative accounting; practice of financial statements; auditor's report